Poverty and social exclusion in North and South : essays on social policy and global poverty reduction - Mosley, Paul.; Dowler, Elizabeth (London ; New York : Routledge, 2003)
Over the past decade there has been a worrying increase in poverty in the industrialised countries of the "North", while many of the developing countries of the "South" have experienced some improvement. This collection argues that there are a number of likenesses between the predicaments of North and South, and that these warrant further investigation and analysis.
Papers presented at a conference held at Sorby Hall, University of Sheffield, on 9 April 2001 and jointly convened by the Development Studies Association of UK and the Political Economy Research Centre (PERC) of the University of Sheffield.
Includes bibliographical references (p. [251]-271) and index.
oif 05/04/16
Loan
Keywords: Poor; Poverty; Marginality, Social; Social policy; Globalization